Influences of Friction Stir Welding and Post‐Weld Heat Treatment on Al–Cu–Li Alloy. Issue 2 (10th October 2017) - Lin, Yi; Lu, Change; Wei, Chengyang; Zheng, Ziqiao
Abstract : In this paper, the influences of friction stir welding (FSW) and post‐weld heat treatment (PWHT) on the microstructures and tensile properties of Al–Cu–Li alloy are investigated. After FSW, strengthen loss occurred in the welding area. Remarkable softening occurs in the thermo‐mechanically affected zone (TMAZ) resulting from dissolution of Al3 Li ( δ ′) phases. Recrystallization and precipitation of ultra‐fine δ ′ phases take place in the nugget zone (NZ) that lightens the softening degree of this zone. A noteworthy enhancement in the hardness and tensile strength of the joint is achieved after T8 reaging treatment (3% − pre‐deformation, 30 h at 152 °C). However, re‐solution treatment coupled with re‐aging treatment leads to ductility deterioration in the joint because coplanar slip of coarse Al3 Li phases induces severe stress concentration during plastic deformation. Abstract : The paper investigates the microstructure and mechanical properties evolution of Al–Cu–Li alloy during FSW and PHWTs. The results show that dissolution of strengthening phases induces the strength loss after FSW, and the T8 re‐aging treatment can effectively enhances the strength of joint without the ductility being excessively deteriorated.